2021
DOI: 10.21203/rs.3.rs-135051/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Biomolecules in Cochineal Dyed Archaeological Textiles by Surface-Enhanced Raman Spectroscopy.

Abstract: SERS spectroscopy is successfully employed in this work to reveal different components integrating the cochineal colorant employed for dying archaeological textile samples from the Arica region in North Chile. This analysis was done by in-situ experiments that does not imply the material (colorant and biomolecules) extraction. The spectroscopic analysis of the archaeological textiles by SERS reveals the presence of bands attributed to carminic acid and nucleobases, mainly adenine and guanine. The identificatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…When comparing our results with previous molecular identification of red dyes in neighboring regions, we found that in the north in southern Peru purpurin from a plant from Relbunium species and carminic acid from cochineal were reported for the Late Intermediate period (1000-1450 A.D.) [54]. The use of cochineal (carminic acid) was also recently reported in Formative textiles from Arica locality to the north of Tarapacá region studied, but without more precision to archaeological context [73]; while only purpurin was identified at San Pedro de Atacama to the eastern south, for the Middle (600-1000 A.D.) and Late Intermediate periods (1000-1450 A.D.) [63]. In the case of the Tarapacá region, only alizarin and carminic acid have been continuously used for a long time.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…When comparing our results with previous molecular identification of red dyes in neighboring regions, we found that in the north in southern Peru purpurin from a plant from Relbunium species and carminic acid from cochineal were reported for the Late Intermediate period (1000-1450 A.D.) [54]. The use of cochineal (carminic acid) was also recently reported in Formative textiles from Arica locality to the north of Tarapacá region studied, but without more precision to archaeological context [73]; while only purpurin was identified at San Pedro de Atacama to the eastern south, for the Middle (600-1000 A.D.) and Late Intermediate periods (1000-1450 A.D.) [63]. In the case of the Tarapacá region, only alizarin and carminic acid have been continuously used for a long time.…”
Section: Discussionsupporting
confidence: 70%
“…From an analytical perspective, they applied chromatographic or spectrometric techniques including gas chromatography-mass spectrometry (GC-MS), high-performance liquid chromatography with diode array detectors (HPLC-DAD) and/or mass spectrometry (HPLC-MS), direct analysis in real time mass spectrometry (DART-MS), which albeit sensitive are destructive methods [3, 48-50, 53, 54, 56-60, 62-64, 66, 70]. Analysis by surface-enhanced Raman spectroscopy (SERS) was applied in just five publications to analyze archaeological textiles from Peru and northern Chile [55,61,65,69,73]. Finally, the available literature shows a particular emphasis on the analysis of polychrome textiles from the Paracas and Nazca cultures (700 BC-800AD), on South-Central Perú [51-53, 59-61, 66, 67, 70].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation